Understanding the origin of early-type dwarfs: the spectrophotometric study of CGCG014−074 - Guevara, Natalia (2024)
Early-type dwarf galaxies constitute a prevalent population in the central regions of rich groups and clusters in the local Universe. These low-luminosity and low-mass stellar systems play a fundamental role in the assembly of the luminous galaxies observed today, according to the ΛCDM hierarchical theory. The origin of early-type dwarfs has been linked to the transformation of disk galaxies interacting with the intracluster medium, especially in dense environments. However, the existence of low-luminosity early-type galaxies in low-density environments presents a challenge to this scenario. This study presents a comprehensive photometric and spectroscopic analysis of the early-type dwarf galaxy CGCG014-074 using deep GEMINI+GMOS data, focusing on its peculiarities and evolutionary implications. CGCG014-074 exhibits distinct features, including a rotating inner disk, an extended stellar formation with a quiescent phase since about 2 Gyr ago, and the presence of boxy isophotes. From the kinematic analysis, we confirm CGCG014-074 as a nucleated early-type dwarf galaxy with embedded disk. The study of its stellar population parameters using different methods provides significant insights into the galaxy´s evolutionary history. These results show an old and metal-poor nucleus (~9.3 Gyr and [Z/H] ~ -0.84 dex), while the stellar disk is younger (~4.4 Gyr) with a higher metallicity ([Z/H] ~ -0.40 dex). These distinctive features collectively position CGCG014-074 as a likely building block galaxy that has evolved passively throughout its history.